Investigate flow characteristics of Metered-Dose Inhaler (MDI) Disposable Inhaler Spacer (AeroCup) for COVID-19 patient by using Computational Fluid Dynamic (CFD) - Abd Rahman, Muhammad Faqhrurrazi; Asmuin, Nor Zelawati; Taib, Ishkrizat; Nazar, Juwaidi; Ismail, Azizan; Khairulfuaad, Riyadhthusollehan (Penerbit Akademia Baru, 2020)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory coronavirus2 syndrome (SARS-CoV-2) were first reported by officials in Wuhan City, China, in December 2019. COVID-19 patients have a symptom of respiratory pneumonia diseases which have difficulties in breathing normally. Previously, the nebulizer machine commonly used to treat respiratory pneumonia diseases. However, the usage for this machine was not suggested during this COVID-19 period because the virus will be spread off easily. To overcome these shortcomings, the uses of Metered-Dose Inhaler (MDI) with MDI disposable inhaler spacer is preferable. Besides, it had been known that the used of MDI disposable inhaler spacer helps to increase the uptaking of the drug into the lung. Besides that, the high demand for the MDI Disposable Inhaler Spacer in the hospital, causing a shortage of supply in Malaysia. Thus, this study aims to produce a new design of this spacer to full fill the market need. This new design of MDI Disposable Inhaler Spacer (AeroCup) was designed by using Solid Work 2018. Then, the parameters for flow characteristic such as particle velocity magnitude, velocity, Eddy viscosity, turbulence Eddy dissipation and turbulence kinetic energy (TKE) was successfully characterized and compared with commercial design A using ANSYS Fluent Version 19.2. The result showed that new design (AeroCup) had the desired characteristic, which was almost similar to commercial design A. This study can provide a piece of information to produce the low-cost metered-dose inhaler (MDI) disposable inhaler spacer to enlighten the burden shouldered by front liners, especially during the pandemic and also can scale-up the economic viability.